Perception of Stakeholders on Abandoned Housing Projects in Malaysia - Ariffin, Noraini Mohd; Razak, Dzuljastri Abdul; Imtiyaz, Mohamed Noorden Mohamed (International Journal of Islamic Economics and Finance (IJIEF), 2019)
Home is a basicnecessity for everyone. However, one of the major issues affecting the construction industry in Malaysia today is that of abandoned housing projects. This issue has caused sufferings to the individuals and society. Several reasons have been cited for the abandoned housing projects, which include the debt financing structure, lack of justice and fairness, and weak regulatory system. The issues of the Islamic banking debt-based home financing products have remained prominent. There are also other issues such as role of the authority in addressing the situations. This study used mixed method of surveys and interviews in determining the perceptions of stakeholders regarding abandoned housing projects in Malaysia. The outcome of study highlights various prospects of mitigating the problem of abandoned housing projects. The findings show that the main cause of abandoned housing project from the interview with the relevant stakeholders is still due to insufficient legal provisions and protection to avoid and prevent abandonment of the housing projects, which is consistent with the previous studies.Â